Sildenafil for pulmonary hypertension treatment after cardiac surgery - Bentlin, Maria Regina [UNESP]; Saito, Adriana [UNESP]; De Luca, Ana Karina C. [UNESP]; Bossolan, Grasiela [UNESP]; Bonatto, Rossano César [UNESP]; Martins, Antonio Sérgio [UNESP]; Rugolo, Ligia Maria Suppo de Souza [UNESP] (Fundacao Sociedade Brasileira de Pediatria, 2005)
Objective: To report on the use of sildenafil for pulmonary hypertension treatment of a newborn patient after cardiac surgery. Description: A female, full term newborn infant with diagnosis of double outlet right ventricle, pulmonary hypoplasia and subaortic ventricular septal defect, was submitted to Blalock surgery in the first week of life. In postoperative the newborn had pulmonary hypertension and persistent hypoxia, without response to nitric oxide, but with improved oxygenation after continuous intravenous infusion of prostaglandin E1. After several failed attempts to discontinue prostaglandin E1, oral sildenafil was used. There was a decrease in pulmonary vascular resistance with consequent oxygenation improvement and 48 hours later it was possible to discontinue prostaglandin E1 infusion. Comments: Sildenafil can be an alternative therapy for pulmonary hypertension, especially when there is no response to conventional therapy. Copyright © 2005 by Sociedade Brasileira de Pediatria.
Keywords: Prostaglandin; Pulmonary hypertension; Sildenafil; nitric oxide; prostaglandin E1; sildenafil; phosphodiesterase inhibitor; piperazine derivative; Blalock Taussig anastomosis; cardiovascular parameters; case report; diagnostic procedure; drug dose regimen; drug mechanism; female; heart right ventricle double outlet; heart surgery; heart ventricle septum defect; human; hypoxia; lung hypoplasia; newborn; oxygenation; pulmonary hypertension; postoperative period; Cardiac Surgical Procedures; Female; Humans; Hypertension, Pulmonary; Infant, Newborn; Phosphodiesterase Inhibitors; Piperazines; Postoperative Period